Study of boundary layer characteristics during the landfalling of a Nisarga cyclone - Rani P. Pawar; Prajna Priyadarshini; T. Dharmaraj; Dada P. Nade; Mahendra N. Patil; Omkar M. Patil; N. Jeni Victor; Sambhaji M. Pawar; D.G. Kanase; Sunil D. Pawar (Tropical Cyclone Research and Review, 2024)
One of the most important parameters in meteorology is the mean wind profile in the tropical cyclone boundary layer. The vertical profile of wind speed and wind direction were measured during the period of the Nisarga cyclone from May 31st, 2020, to June 5th, 2020, using the newly installed Phased Array Doppler Sodar system at the Center for Space and Atmospheric Science (CSAS), Sanjay Ghodawat University, Kolhapur (16.74° N, 74.37° E; near India's western coast). Our analysis revealed that the maximum mean wind speed was 17 m/s on June 3, 2020, at 10:00 IST. It also shows the change in wind direction from southwest to southeast on June 2 and 3, 2020. Daily high-resolution reanalysis data in the domain, 0–25°N, 65–110°E, during the period from May 31st to June 5th, 2020, revealed the variation of the atmospheric pressure of the Nisarga cyclone from 1000 to 1008 hPa, sea surface temperature (SST) between 30 °C and 31 °C, outgoing longwave radiation (OLR) between 100 and 240 Wm-2, wind speed between 3 and 15 m/s, and low values of vertical wind shear (VWS) were observed to the north of Nisarga track. These observations may provide more insights for the study of boundary layer turbulence during cyclonic activities.